Optimization of Liver Decellularization Maintains Extracellular Matrix Micro-Architecture and Composition Predisposing to Effective Cell Seeding. - Panagiotis Maghsoudlou; Fanourios Georgiades; Holly Smith; Anna Milan; Panicos Shangaris; Luca Urbani; Stavros P Loukogeorgakis; Benedetta Lombardi; Giuseppe Mazza; Charlotte Hagen; Neil J Sebire; Mark Turmaine; et al. (PLoS ONE)
Hepatic tissue engineering using decellularized scaffolds is a potential therapeutic alternative to conventional transplantation. However, scaffolds are usually obtained using decellularization protocols that destroy the extracellular matrix (ECM) and hamper clinical translation. We aim to develop a decellularization technique that reliably maintains hepatic microarchitecture and ECM components. Isolated rat livers were decellularized by detergent-enzymatic technique with (EDTA-DET) or without EDTA (DET). Histology, DNA quantification and proteomics confirmed decellularization with further DNA reduction with the addition of EDTA. Quantification, histology, immunostaining, and proteomics demonstrated preservation of extracellular matrix components in both scaffolds with a higher amount of collagen and glycosaminoglycans in the EDTA-DET scaffold. Scanning electron microscopy and X-ray phase contrast imaging showed microarchitecture preservation, with EDTA-DET scaffolds more tightly packed. DET scaffold seeding with a hepatocellular cell line demonstrated complete repopulation in 14 days, with cells proliferating at that time. Decellularization using DET preserves microarchitecture and extracellular matrix components whilst allowing for cell growth for up to 14 days. Addition of EDTA creates a denser, more compact matrix. Transplantation of the scaffolds and scaling up of the methodology are the next steps for successful hepatic tissue engineering.